Meta-analysis of the effects of calcium phosphate bone tissue engineering scaffolds on orthodontic bone augmentation and tooth movement - Zhao, Jiawen; Liu, Xuefei; Zhang, Qi; Jin, Yinan; Zhao, Gang (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveIn oral clinical treatment, adequate alveolar bone volume is a crucial prerequisite for expanding the indications of orthodontic treatment and achieving functional and aesthetic reproduction during the tooth movement process. Therefore, before treating orthodontic patients with insufficient alveolar bone volume, alveolar bone augmentation is necessary to provide the necessary conditions for the safe and effective movement of teeth to the precise target position. This study aims to investigate the three-dimensional reconstruction effect of bone tissue in orthodontic alveolar bone defects using calcium phosphate bioactive ceramic materials, as well as the feasibility of normal tooth movement within the bone regeneration area.MethodsArticles related to the use of calcium phosphate bioactive ceramic materials for bone grafting in orthodontic alveolar bone defect models were retrieved from CNKI, Wanfang, VIP, China Biomedical Literature Database, PubMed, Embase, Cochrane Library, and Web of Science. The search was conducted up to 1 March 2024. Two researchers independently extracted data, and the SYRCLE animal bias risk assessment tool was used for literature quality evaluation. Meta-analysis of outcome measures was performed using RevMan 5.4 and Stata 15.1 software.ResultsA total of 16 randomized controlled animal studies were included, with an overall moderate quality rating. Meta-analysis showed no significant differences between the intervention and control groups for the following outcomes: BMD (SMD = 1.88, 95% CI: −2.84 to 6.60, p = 0.44), new bone formation percentage (SMD = −0.11, 95% CI: −1.38 to 1.16, p = 0.86), OTM (SMD = −0.11, 95% CI: −0.96 to 0.75, p = 0.81), RR (SMD = 0.18, 95% CI: −1.87 to 2.24, p = 0.86), pressure side osteoclast count (SMD = 0.33, 95% CI: −0.30 to 0.95, p = 0.31), and tension side BMP2 levels (SMD = 0.46, 95% CI: −0.25 to 1.18, p = 0.20). However, BV/TV (SMD = 2.15, 95% CI: 1.17 to 3.14, p = 0.0001) was significantly increased. Egger’s test indicated a potential publication bias (P = 0.000 < 0.05), suggesting caution in interpreting this result.ConclusionCurrent animal studies indicate no significant differences between the calcium phosphate bioactive ceramic material group and the control group in orthodontic alveolar bone defect repair. Orthodontic tooth movement after alveolar bone defect repair is feasible.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/